"Expect it and accept it: coping with islamophobia in The Canadian medical field" - Bullock, Katherine (The Palgrave handbook of gendered Islamophobia, 2024)
In this chapter I look at how Canadian Muslim healthcare workers cope with Islamophobia at work. I partnered with the Muslim Medical Association of Canada. I interviewed eleven health care workers, men and women, from across Canada. We talked about the incident(s) they have faced, how they reacted at the time, how they coped afterwards, and how it/they affected their daily life subsequently. Surprisingly many interviewees reported Islamophobic incidents from colleagues, teachers and supervisors. Interviewees reported a range of negative emotions linked to the incidents. Positive and negative coping strategies included: Peer Support; Avoidance; Faith; Collegial Feedback; Official Reporting; and Advocacy. This is the first study to examine Canadian Muslim healthcare workers’ experiences of anti-Muslim racism and how they coped.